Pengaruh BOPO Terhadap Tingkat Bagi Hasil Deposito Mudharabah BUS Periode 2015-2019 dengan ROA Sebagai Mediasi - Ariya Mutika; Endah Susilowati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
The profit sharing rate for mudharabah deposits is a type of investment in rupiah or foreign currency which withdrawals are made at payment due date using the mudharabah (profit sharing) principle. The purpose of this study is to analyze the effect of Operating Expenses on Operating Income (BOPO) on the profit sharing rate of mudharabah deposits in Islamic commercial banks registered with the OJK in 2015-2019 through ROA as an intervening variable. The method of determining the sample using purposive sampling technique, in order to obtain a sample of 12 Islamic banks with 60 observation data. The type of data used is secondary data from the annual reports of Islamic Commercial Banks. Data analysis using SEM PLS with WarpPLS 7.0 software program. The results of the study prove that BOPO has a significant effect on ROA. Meanwhile, BOPO and ROA do not have effect on the profit sharing rate of mudharabah deposits, and BOPO does not have effect on the profit sharing rate of mudharabah deposits through ROA.